Punishment for murder convicts: a comparative study between shariah and Malaysian criminal law / Mohd Faizal Nizam Mohd Fuad ... [et al.] - Mohd Fuad, Mohd Faizal Nizam; Hussain, Mohd Badrulzaman; Badrul Hisham, Nor Humairah; Ismail, Nor Nabiha Nadia (2010)
This research paper has been conducted in relation of the issue of the punishment with regards to murder convicts under the Malaysian and the Shariah Criminal Law. Under the Malaysian Criminal Law, the punishment is embodied under section 302 of the Penal Code and section 277 of Criminal Procedure Code where whoever commits murder shall be punished with death sentence and the method of execution is by hanging by the neck until death. Under the Shariah Criminal Law, similar punishment i.e. death penalty is provided for the offence of murder under Qisas. In addition, there are options given to the heir of the victim where they can opt for retaliation, compensation or pardon in order to punish the convict. In the finding, it was found that death penalty, despite being the most severe punishment is not able to curb the increasing number of murder cases. In a nutshell, the implementation of the gist of Qisas under the Malaysian Criminal Law though quite controversial, can be an alternative to death penalty which may bring more benefit to the society.